ASME 2004 Internal Combustion Engine Division Fall Technical Conference 2004
DOI: 10.1115/icef2004-0837
|View full text |Cite
|
Sign up to set email alerts
|

CFD Modeling of Pilot Injection and EGR in DI Diesel Engines

Abstract: The simulation of direct injection diesel engines requires accurate models to predict spray evolution and combustion processes. Several models have been proposed and widely tested for traditional injection strategies characterized by single injection pulse close to top dead center. Unfortunately, these models show some limits when applied to different injection strategies so that a correct simulation of engine performances and emission cannot be achieved without changing variables included in spray and combust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…for a single operating mode [15]- [16]- [17]. De Risi et al [7]- [4]- [5] found that the effectiveness of a particular combustion chamber in reducing emissions depends on engine load and operating conditions, which means that engines need to be optimized for different operating conditions. Senecal et al [14] applied the KIVA-GA method to optimize the chamber design for two operating modes.…”
Section: Introductionmentioning
confidence: 99%
“…for a single operating mode [15]- [16]- [17]. De Risi et al [7]- [4]- [5] found that the effectiveness of a particular combustion chamber in reducing emissions depends on engine load and operating conditions, which means that engines need to be optimized for different operating conditions. Senecal et al [14] applied the KIVA-GA method to optimize the chamber design for two operating modes.…”
Section: Introductionmentioning
confidence: 99%